(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses Tahir Malik’s “Alvido Bolalik” and the sociolects, or slang, utilized in it. It also discusses the manners employed in the creative work’s speech acts.